1999
DOI: 10.1007/s100510050907
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative study of laterally inhomogeneous wetting films

Abstract: Based on a microscopic density functional theory we calculate the internal structure of the three-phase contact line between liquid, vapor, and a confining wall as well as the morphology of liquid wetting films on a substrate exhibiting a chemical step. We present a refined numerical analysis of the nonlocal density functional which describes the interface morphologies and the corresponding line tensions. These results are compared with those predicted by a more simple phenomenological interface displacement m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
119
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(130 citation statements)
references
References 38 publications
11
119
0
Order By: Relevance
“…(33) permits us finding the partial derivative (∂κ/∂r) T , from the linear adsorption value Λ and the derivatives dκ/dr and dµ/dr along equilibrium states. For example, such calculations are possible by applying the density functional method based on the models for intermolecular potentials [10,11,20] and by applying the method of the functional of the local thickness of a liquid film based on the approximations for the isotherm of the disjoining pressure as a function of the film thickness [8,9,11]. Both these methods are capable of independent calculating the contact angle, the chemical potential of molecules in a system and the linear adsorption as functions of the dividing line radius.…”
Section: The Role Of Linear Adsorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…(33) permits us finding the partial derivative (∂κ/∂r) T , from the linear adsorption value Λ and the derivatives dκ/dr and dµ/dr along equilibrium states. For example, such calculations are possible by applying the density functional method based on the models for intermolecular potentials [10,11,20] and by applying the method of the functional of the local thickness of a liquid film based on the approximations for the isotherm of the disjoining pressure as a function of the film thickness [8,9,11]. Both these methods are capable of independent calculating the contact angle, the chemical potential of molecules in a system and the linear adsorption as functions of the dividing line radius.…”
Section: The Role Of Linear Adsorptionmentioning
confidence: 99%
“…Among them, a generalized Neumann-Young equation was obtained [6], the concept of line of tension was introduced [7], the theories of line tension based on different approaches to the detailed description of the system were developed and several estimates of the value of the line tension were presented [8][9][10][11][12], the stability conditions were examined and the possibility of line tension to have positive or negative values was commented [13][14][15]. New experimental methods for measuring the line tension were described and different applications of the line tension concept to the theories of formation of thin films, flotation, heterogeneous nucleation were found.…”
Section: Introductionmentioning
confidence: 99%
“…Since nucleation phenomena deal with nuclei of nanoscopic size, in the case of wall-attached nuclei the effect of the line tension of the three-phase contact line (where the interface between the coexisting phases meets the wall [36][37][38][39][40][41][42]) must not be neglected. In the present paper, where we apply a Monte Carlo computer simulation approach [43][44][45] and thus necessarily deal with finite systems and therefore need to address finite size effects [43][44][45][46][47]), it is hence necessary to include the possibility of line tension effects in the analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Recent experimental and theoretical studies have shown that structured substrates exhibit a variety of novel adsorption properties which not only promise to be of importance to future technologies such as microfluidics [2], but are also of fundamental interest to statistical physics [3]. In particular, the effect of chemical inhomogeneities has been addressed recently in different contexts, for example: contact angles of liquid drops [4][5][6], droplet spreading [7], morphological phase transitions [8], three phase contact line [9], Cassie's law [10,11], drop shapes [12], construction of magnetic materials [13], microscopic packing [14], liquid channels [15], polymer blends [16,17], and dewetting [18], among others.…”
Section: Introductionmentioning
confidence: 99%